The timing and importance of arboriculture and agroforestry in a temperate East Polynesia Society, the Moriori, Rekohu (Chatham Island). (1st October 2016) - Maxwell, Justin J.; Howarth, Jamie D.; Vandergoes, Marcus J.; Jacobsen, Geraldine E.; Barber, Ian G.
Abstract: Identifying arboriculture and agroforestry in Polynesian Societies has usually relied heavily upon the ethnographic record in the absence of direct archaeological evidence. In this paper we outline a multi-proxy research design, including ethnography, palynology, anthracology, archaeology and a high precision chronology to evaluate arboriculture and agroforestry as components of Moriori subsistence practices before the arrival of Europeans in 1791. The colonisers of Rekohu brought with them a mainland New Zealand endemic tree, Corynocarpus laevigatus, and the technology to propagate the tree in a less than ideal climate and to process its drupe into a storable source of carbohydrate in what was a difficult environment for Polynesian cultivation practices. We also present a conceptual model of forest change due to Moriori fuel selection practices which suggests that Moriori were actively managing these forest spaces for food, fuel, medicine, construction material and as a habitation space, therefore making agroforestry an important component of Moriori subsistence. Highlights: Investigating arboriculture and agroforestry in Moriori subsistence practices. Anthracology, ethnography and palynology as evidence of arboriculture and agroforestry. High precision chronology of anthropogenic vegetation change on Rekohu (Chatham Island). A conceptual model of forest change due to Moriori fuel selection practices.